Correlation of Body Mass Index, Physical Activity, and Physical Fitness in Elementary School Students - Ilmul Ma’arif; Nurhasan; Suroto; Risfandi Setyawan; Basuki; Mohammad Zaim Zen; Rahayu Prasetiyo; Yudi Dwi Saputra; Novita Nur Synthiawati (Physical Education Theory and Methodology, 2023)
The purpose of this study was to determine the conditions and the relationship between body mass index (BMI), physical activity, and physical fitness.